Lanthanide(III) (Eu, Gd, Tb, Dy) Complexes Derived from 4‐(Pyridin‐2‐yl)methyleneamino‐1,2,4‐triazole: Crystal Structure, Magnetic Properties, and Photoluminescence - Bazhina, Evgeniya S.; Bovkunova, Anna A.; Medved'ko, Alexey V.; Varaksina, Evgeniya A.; Taidakov, Ilya V.; Efimov, Nikolay N.; Kiskin, Mikhail A.; Eremenko, Igor L. (Chemistry, an Asian journal, 2018)
The reaction of lanthanide(III) nitrates with 4‐(pyridin‐2‐yl)methyleneamino‐1,2,4‐triazole (L) was studied. The compounds [Ln(NO3)3(H2O)3]⋅2 L, in which Ln=Eu (1), Gd (2), Tb (3), or Dy (4), obtained in a mixture of MeCN/EtOH have the same structure, as shown by XRD. In the crystals of these compounds, the mononuclear complex units [Ln(NO3)3(H2O)3] are linked to L molecules through intermolecular hydrogen‐bonding interactions to form a 2D polymeric supramolecular architecture. An investigation into the optical characteristics of the Eu3+‐, Tb3+‐, and Dy3+‐containing compounds (1, 3, and 4) showed that these complexes displayed metal‐centered luminescence. According to magnetic measurements, compound 4 exhibits single‐ion magnet behavior, with ΔEeff/kB=86 K in a field of 1500 Oe. Shell replacement: Lanthanide compounds are synthesized as analogues of lanthanide nitrate hydrates, in which hydrate water molecules are replaced by the organic ligand (L). The replacement of hydrate water molecules by L leads to changes in the coordination number (from 10 to 9), the polyhedral geometry, and magnetic characteristics (see figure).